Infections in children with acute myeloid leukemia: increased mortality in relapsed/refractory patients. Issue 12 (15th October 2019) - Zając-Spychała, Olga; Skalska-Sadowska, Jolanta; Wachowiak, Jacek; Szmydki-Baran, Anna; Hutnik, Łukasz; Matysiak, Michał; Pierlejewski, Filip; Młynarski, Wojciech; Czyżewski, Krzysztof; Dziedzic, Magdalena; Wysocki, Mariusz; Zalas-Więcek, Patrycja; et al.
Abstract: The aim of this nationwide study was to describe the epidemiology and profile of bacterial infections (BI), invasive fungal disease (IFD) and viral infections (VI) in patients with de novo and relapsed/refractory (rel/ref) acute myeloid leukemia (AML). Within the studied group of 250 children with primary AML, at least one infectious complication (IC) was diagnosed in 76.0% ( n = 190) children including 85.1% ( n = 504) episodes of BI, 8.3% ( n = 49) – IFD and 6.6% ( n = 39) – VI. Among 61 patients with rel/ref AML, at least one IC was found in 67.2% ( n = 41) of children including 78.8% ( n = 78) of BI, 14.1% ( n = 14) of IFD and 7.1% ( n = 7) of VI. In all AML patients, within BI Gram-negative strains were predominant. Half of these strains were multi-drug resistant. Characteristics of IFD and VI were comparable for de novo and rel/ref AML. The infection-related mortality was significantly higher, while survival from infection was significantly lower in patients with rel/ref disease.